Spatially resolved star formation and metallicity profiles in post-merger galaxies from MaNGA. (3rd October 2018) - Thorp, Mallory D; Ellison, Sara L; Simard, Luc; Sánchez, Sebastian F; Antonio, Braulio
ABSTRACT: Large galaxy surveys have demonstrated that galaxy–galaxy mergers can dramatically change the morphologies, star formation rates (SFRs), and metallicities of their constituents. However, most statistical studies have been limited to the measurement of global quantities, through large fibres or integrated colours. In this work, we present the first statistically significant study of spatially resolved star formation and metallicity profiles using integral field spectroscopy, using a sample of ∼20 000 spaxels in 36 visually selected post-merger galaxies from the Mapping Nearby Galaxies at Apache Point Observatory survey. By measuring offsets from SFR and metallicity scaling relations on a spaxel-by-spaxel basis, we are able to quantify where in the galaxy these properties are most affected by the interaction. We find that the SFR enhancements are generally centrally peaked, by a factor of 2.5 on average, in agreement with predictions from simulations. However, there is considerable variation in the SFR behaviour in the galactic outskirts, where both enhancement and suppression are seen. The median SFR remains enhanced by 0.1 dex out to at least 1.9 R e . The metallicity is also affected out to these large radii, typically showing a suppression of ∼−0.04 dex.